Revisiting the Exchange Rate Pass- Through to Domestic Prices in Egypt - Abdelhamid, Ahmed (AUC Knowledge Fountain, 2023)
Exchange rate pass-through (ERPT) refers to the extent to which the movements in the exchange rate influence domestic prices. This study revisits the exchange rate pass-through in Egypt using quarter data from 2006 to 2022. The study employs a Structural Vector Autoregression (SVAR) model to estimate the degree of ERPT. The findings suggest that ERPT in Egypt is incomplete, meaning that changes in the exchange rate do not fully pass through to consumer prices. The study also investigates the role of the money supply in absorbing the shocks in the nominal exchange rate. The study has important implications for policymakers in Egypt, as a better understanding of ERPT can help them to design effective monetary and exchange rate policies.